> 数学 >
[(-3ab)²×a³+2a³×(-3ab)³×1/2b]÷(3a²b²)² ,其中a=1/3,b=-
b=-(1/2)
人气:318 ℃ 时间:2019-10-11 01:01:29
解答
[(-3ab)²×a³+2a³×(-3ab)³×1/2b]÷(3a²b²)²
=[-3a^5b^2-3a^6b^2]÷9a^4b^4
=-a/3b^2-a^2/3b^2
=-a/3b^2*(a-1)
=-a/3b^2*0
=0好像不对[(-3ab)²×a³+2a³×(-3ab)³×1/2b]÷(3a²b²)² =[-3a^5b^2-27a^6b^2]÷9a^4b^4=-a/3b^2-3a^2/b^2=-a/3b^2*(a-9)b等于什么?b=负二分之一[(-3ab)²×a³+2a³×(-3ab)³×1/2b]÷(3a²b²)² =[9a^5b^2-27a^6b^2]÷9a^4b^4=a/b^2-3a^2/b^2=a/b^2*(1-3a)=1/(-1/2)^2*(1-3)=1/(1/4)*(-2)=4*(-2)=-8
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版